Od akrostychu do akrokonstrukcji (z historii rosyjskiej poezji wizualnej) - NDiaye, Iwona Anna; Chudasov, Ivan (Acta Polono-Ruthenica, 2010)
From time, when verses begun to be written down, sound involuntarily began to be united with the letter, but if to remind hieroglyphic literature, also with the picture. Does not surprise therefore fact, that with the flow of time appeared verses, exclusively adjusted on optic reception. Among them particularly popular fixed itself acrostic versified compositions, in which certain from the columns of letters, syllables or words created additionally the all words, sentence or opinion. Most often such columns are read from the bottom, from the top, or alternatively, were created by the first or last succeeding letters of the verse, or also could be described through so- called middle, that is to say other elements of the verses inside division. In Russian literature acrostic were applied from 17th century. In the former history of literature acrostic did not enroll as the kind of high literature, at least examples we can find in poetry of S. Po³ocki, W. Brusow, I. Siewierianin, N. Gumilow, B. Pasternak and many other Russian poets. As a consequence of these past methods to the sphere of refined poetry and poetic tricks, and in such state are found up to now. In principle acrostic in this form, in what it still existed, was used up. However in new poetry acrostic can renew itself in the new quality within the framework, for example, of non logical verse. Besides that, the practical use of acrostic has large perspectives. We can suppose, that this form of poetic recording has before itself future in the sphere of dedication, greetings and advertisings.